Satisfaction and Motivation of Nursing Professional: A Study on Rangpur Medical College Hospital - Khan, Mohammad Rafiul Azam; Rahman, Mohammad Azizur; Hossain, Zahid (Archives of Business Research, 2022)
Services of nursing professional play a pivotal role in health organizations to support patients and doctors. The study was exploratory in nature with the view to observe the relationship between motivation and job satisfaction of nursing professional. It tried to unfold the underlying factors and the degree of influence of motivational factors for job satisfaction to achieve the main objective. The study used one hundred and two (102) nurses as samples from Rangpur Medical College Hospital in Bangladesh. It used Exploratory Factor Analysis (EFA) and Structural Equation Model (SEM) to reach to a meaningful conclusion. The paper found that the intrinsic factors affect the behavioral actions of the nurses towards job satisfaction. It also revealed that nurses face some significant problems relating to promotion, training, career development, workload etc. Enhancing job satisfaction to improve performance, efficiency, productivity of the nurses’ hospital management authority is urged to look into the motivational factors more closely suggested in the study. The study may assist the policy makers, administrators, and human resources experts to search for new opportunities and policies to encounter job satisfaction for nursing professionals.